Comparative Analysis of BTM Systems Made of a Fireproof Composite Material with Nano Boron Nitride - Ioan Szabo; Florin Mariasiu; Thomas Imre Cyrille Buidin (Fire)
The paper presents a numerical analysis of the possibilities of replacing the aluminum serpentines in the current construction of battery thermal management systems (BTMS) with cooling serpentines made of fireproof composite materials with high heat transfer parameters (fireproof epoxy resin + nano boron nitride). This approach was given by the need to replace aluminum (which, in case of fire, maintains and accelerates the combustion process) with fireproof materials that reduce/eliminate the fire risk due to improper battery operation. Numerical analysis methods were used through simulation to identify the most efficient design among the single-channel, multichannel, multiflow and multiple coolant inlet–outlet solutions for cooling serpentine. In addition to these geometric constructive parameters, the variation of the coolant flow rate (9, 12, 15 and 18 L/min) and coolant inlet temperature (17, 20 and 25 °C) was also considered. The obtained results showed that the single-inlet nanocomposite resin cooling serpentine four-channel configuration presents the highest cooling efficiency of the cells that form the battery module while ensuring very good thermal uniformity as well. These findings are supported by the lowest average heat absorption by the batteries, of 34.44 kJ, as well as the lowest average internal resistance difference (caused by thermal gradients), of 5.23%. Future research is needed to identify the degree of structural resistance of serpentines made of fireproof composite material to external stresses (vibrations characteristic of the operation of electric vehicles).